PROBLEM BASED LEARNING (PBL)APPROACH THROUGH MAZE GAMES TO IMPROVE CRICAL THINKING SKILLS IN EARLY CHILDHOOD - Hasnaini; Herlina; Azizah Amal; Wahira (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
Problem-based learning is primarily designed to help students develop their thinking skills, problem-solving skills, and intellectual skills; learn adult roles by experiencing them through various real or simulated situations; and become independent learners. This study used a quasi-experimental method. The type of research design used was a Nonequivalent Control Group Design, with two research groups: an experimental group receiving treatment and a control group not receiving experimental treatment. Data collection techniques used observation and documentation. Data analysis techniques used descriptive analysis and non-parametric statistical analysis. The Problem-Based Learning (PBL) approach through maze games had a positive and significant effect on children's critical thinking skills. This was evidenced by the difference in the increase in critical thinking skills between the experimental and control groups, and was reinforced by the results of statistical analysis and conformity with theories and previous research stating that PBL is effective in developing critical thinking skills as part of higher-order thinking skills. The continuous implementation of the PBL approach can be one effort to improve the quality of the learning process in early childhood education.